Determinants of Purchasing Decisions at Warung Baleganjur: Moderated by Celebrity Endorsement - Komang Bagus Trivikrama Kumara; Gede Suparna (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Purchasing decisions are one of the actions based on several alternative choices to make a purchase of a product based on awareness of needs and desires. Analysis of purchasing decisions is very important because there is a phenomenon of consumer visits to Warung Baleganjur remaining busy but there is a decrease in sales. This study aims to test the role of brand image in mediating the influence of social media marketing on purchasing decisions moderated by celebrity endorsements. The population in this study were buyers at Warung Baleganjur in Denpasar City. The sample used in this study was 108 respondents. The sampling method used in this study was the non-probability method with the purposive sampling technique. Data collection was carried out by distributing questionnaires online via Google Forms. The collected data were analyzed using classical assumption test, path analysis technique, Sobel test and VAF test and Moderated Regression Analysis (MRA) with the help of SPSS 25 application. The results of this study indicate that social media marketing has a positive and significant effect on purchasing decisions, social media marketing has a positive and significant effect on brand image, brand image has a positive and significant effect on purchasing decisions, brand image is able to partially mediate the effect of social media marketing on purchasing decisions, and celebrity endorsement is unable to moderate the effect of social media marketing on purchasing decisions at Warung Baleganjur. The implications of this study can be used as consideration and input for Warung Baleganjur in improving consumer purchasing decisions by considering the variables of social media marketing, brand image, and celebrity endorsement.